2017
DOI: 10.1161/jaha.117.007058
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Childbirth Is Associated With Greater Framingham Risk Scores for Cardiovascular Disease Among Participants of the IMIAS (International Mobility in Aging Study)

Abstract: BackgroundPrevious studies observe associations between lifetime parity and cardiovascular disease, but relatively fewer investigate age at first childbirth (AFB). Herein, we examine the association of AFB with a summary cardiovascular risk measure (Framingham Risk Score [FRS]).Methods and ResultsAs part of the IMIAS (International Mobility in Aging Study), data were collected in 2012 among 1047 women, aged 65 to 74 years, from Canada, Albania, Colombia, and Brazil. FRSs were calculated to describe cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…A gradual increase in low-grade albuminuria (protein in urine, a marker of an increased risk of cardiovascular health problems) with parity was observed in women from China [42]. Giving birth early (at less than 20 years of age) also contributes to a greater overall cardiovascular risk in older age [43].…”
Section: Does Reproduction Have a Long-term Negative Impact? Health And Age-related Diseasesmentioning
confidence: 99%
“…A gradual increase in low-grade albuminuria (protein in urine, a marker of an increased risk of cardiovascular health problems) with parity was observed in women from China [42]. Giving birth early (at less than 20 years of age) also contributes to a greater overall cardiovascular risk in older age [43].…”
Section: Does Reproduction Have a Long-term Negative Impact? Health And Age-related Diseasesmentioning
confidence: 99%
“…Child marriage is a key driver of adolescent childbearing that can impact long-term health outcomes of women [4]. Several studies document the association between adolescent childbearing and later life risks of hypertension and cardiovascular diseases [5,6]. A couple of recent studies also report a higher risk of hypertension and other self-reported chronic conditions being associated with child marriage [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Covariate selection (above) for statistical adjustment was determined by previous related research (Baldi et al, 2013; Clark et al, 2009; Rosendaal et al, 2017) and informed our statistical analyses (below). Briefly, predisposing characteristics (age, birthplace, race/ethnicity, and census division) likely influence attitudes and expectations about ideal family size as well as have influences on heart disease probability.…”
Section: Methodsmentioning
confidence: 99%